Fauci : expect the unexpected : ten lessons on truth, service, and the way forward - Fauci, Anthony S., 1940- (National Geographic, 2021)
"Compiled from hours of interviews drawn from the eponymous National Geographic documentary, this inspiring book from world-renowned infectious disease specialist Anthony Fauci shares the lessons that have shaped the celebrated doctor's life philosophy, offering an intimate view of one of the world's greatest medical minds as well as universal advice to live by"--